Intrinsic Photoluminescence of Solid-State Gold Nanoclusters: Towards Fluorescence Lifetime Imaging of Tissue-Like Phantoms Under Two-Photon Near-Infrared Excitation - Hada, Alexandru-Milentie; Craciun, Ana-Maria; Astilean, Simion (Frontiers in Chemistry, 2021)
Gold nanoclusters (AuNCs) have attracted extensive attention as light-emissive materials with unique advantages such as high photostability, large Stoke shifts and low toxicity. However, a better understanding of their solid-state photoluminescence properties is still needed. Herein, we investigated for the first time the intrinsic photoluminescence properties of lyophilized bovine serum albumin stabilized AuNCs (BSA-AuNCs) via fluorescence lifetime imaging microscopy (FLIM) studies performed under both one and two photon excitations (OPE and TPE) on individual microflakes, combined with fluorescence spectroscopic investigations. Both in solution and solid-state, the synthesized BSA-AuNCs exhibit photoluminescence in the first biological window with an absolute quantum yield of 6% and high photostability under continuous irradiation. Moreover, under both OPE and TPE conditions, solid BSA-AuNCs samples exhibited a low degree of photobleaching, while FLIM assays prove the homogeneous distribution of the photoluminescence signal inside the microflakes. Finally, we demonstrate the ability of BSA-AuNCs to perform as reliable bright and photostable contrast agents for the visualization of cancer tissue mimicking agarose-phantoms using FLIM approach under non-invasive TPE. Therefore, our results emphasize the great potential of the as synthesized BSA-AuNCs for ex vivo and in vivo non-invasive NIR imaging applications.